Pharmacological interventions for the treatment of Coronavirus Disease (COVID-19) - Huaroto, Fabiola (2020)
Several drugs have been proposed as therapeutic alternatives for COVID-19. An electronic systematic search of MEDLINE (via PubMed) was carried out until March 20th 2020, in order to identify the available evidence on pharmacological interventions for specific treatment of COVID-19. The quality of the evidence from clinical trials was evaluated according to the GRADE methodology. 947 publications were identified and 15 studies were selected: 3 clinical trials, 5 case series and 7 case reports. The existing evidence for hydroxychloroquine, favipiravir and lopinavir/ritonavir comes from clinical trials reporting favorable results for the first two drugs, while no benefit was observed when lopinavir/ritonavir was added to standard treatment. However, due to methodological issues, the evidence for hydroxychloroquine is very low. For favipiravir and lopinavir/ritonavir the evidence is low. Regarding the use of arbidol interferon, or the combined use of these with lopinavir/ritonavir, the evidence is limited since it derives from case series or case report with non-determining results. No studies were identified that reliably demonstrate the efficacy and safety of any pharmacological intervention against COVID-19.